REPRESENTASI PEREMPUAN DALAM FILM SATRIA DEWA GATOTKACA (ANALISIS SEMIOTIKA) - Cendiberdi, Reza; Priyadi, Antonius Totok; Seli, Sesillia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to examine the representation of women in the film "Satria Dewa: Gatotkaca" and to develop a teaching module as a learning media. The research utilizes a descriptive method with a qualitative research design. The primary source of this research is the film "Satria Dewa: Gatotkaca". The theoretical framework employed to analyze the research problem is semiotic theory. Data collection techniques involve documentary study methods by selecting scenes from the research object. The findings of this study indicate that there are several scenes depicting the representation of women in the film "Satria Dewa: Gatotkaca". The representation of women is observed through signs and meanings analyzed using Roland Barthes' semiotic theory. The implementation of Indonesian language teaching in this study is in the form of a Teaching Module Reviewing Fiction Works in audiovisual format for Grade VII, Second Semester, Junior High School (SMP) under the Merdeka Curriculum.